The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1177/0192513x19837316
|View full text |Cite
|
Sign up to set email alerts
|

Department Environment and Work-to-Life Conflict Among Faculty in the STEM Fields

Abstract: Identifying factors contributing to work-to-life conflict among STEM (science, technology, engineering, and mathematics) faculty members is crucial to improving how STEM faculty manage multiple roles. This study examines how both positive (psychological safety) and negative (perceived injustice) features of the departmental environment predict work-to-life conflict among STEM faculty. We also consider whether gender moderates how each facet of the departmental environment relates to work-to-life conflict. Data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 77 publications
0
11
0
Order By: Relevance
“…Initially the research suggested a chilly climate [18,19], then focused on deficiencies in women's attitudes and behaviors [20] and has now become focused on issues of society, life choices, and bias [21]. The latest research suggests that many of the problems women face are cultural, and similar to what women in leadership positions face: implicit gender bias [22], harassment [23,24], dual-career couple issues [25], imposter syndrome [5,6], home/work balance [26], and lack of sense of belonging [27]. Many of these issues are discussed in references [28,29].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Initially the research suggested a chilly climate [18,19], then focused on deficiencies in women's attitudes and behaviors [20] and has now become focused on issues of society, life choices, and bias [21]. The latest research suggests that many of the problems women face are cultural, and similar to what women in leadership positions face: implicit gender bias [22], harassment [23,24], dual-career couple issues [25], imposter syndrome [5,6], home/work balance [26], and lack of sense of belonging [27]. Many of these issues are discussed in references [28,29].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Timing was crucial, and would likely continue to be important, especially in relation to planning a family; this will be a key aspect to consider as transitions to midcareer or into leadership roles for these women and potential impacts of family (Beddoes & Pawley, 2014;Howe-Walsh & Turnbull, 2016;Rafnsdóttir & Heijstra, 2013;Toader, 2018;Minnotte & Pedersen. 2019;Shreffler et al, 2019).…”
Section: Short-term Emergence Of Academic Identitiesmentioning
confidence: 99%
“…The third is work-life balance. An increasing number of studies have focused on work-family issues for women in STEM fields, such as software professionals [30] and faculty in STEM departments [31]. Jean et al [32] provided comprehensive reviews on women's family issues in STEM fields.…”
Section: A Brief Review Of Literature On Gender Differences In Major Choicementioning
confidence: 99%